2007
DOI: 10.1016/j.yfrne.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Topography in the preoptic region: Differential regulation of appetitive and consummatory male sexual behaviors

Abstract: Several studies have suggested dissociations between neural circuits underlying the expression of appetitive (i.e. sexual motivation) and consummatory components (i.e., copulatory behavior) of vertebrate male sexual behavior. The medial preoptic area (mPOA) clearly controls the expression of male copulation but, according to a number of experiments, is not necessarily implicated in the expression of appetitive sexual behavior. In rats for example, lesions to the mPOA eliminate maletypical copulatory behavior b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
171
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(187 citation statements)
references
References 138 publications
(210 reference statements)
16
171
0
Order By: Relevance
“…In quail, a large number of studies based on stereotaxic electrolytic lesions [9,16] or steroid implantation [15,17] have confirmed the critical role of this nucleus in the regulation of male sexual behavior [11]. The present study provides additional confirmation that the mPOA is involved in the expression of male sexual behavior given that a significant increase in Fos expression was found in this area in birds that had copulated with a female as compared to birds that remained in their home cages.…”
Section: Effects Of Anosmia And/or Cloacal Gland Anesthesia On Fos Exsupporting
confidence: 77%
See 1 more Smart Citation
“…In quail, a large number of studies based on stereotaxic electrolytic lesions [9,16] or steroid implantation [15,17] have confirmed the critical role of this nucleus in the regulation of male sexual behavior [11]. The present study provides additional confirmation that the mPOA is involved in the expression of male sexual behavior given that a significant increase in Fos expression was found in this area in birds that had copulated with a female as compared to birds that remained in their home cages.…”
Section: Effects Of Anosmia And/or Cloacal Gland Anesthesia On Fos Exsupporting
confidence: 77%
“…The medial preoptic area (mPOA) is also a key site for the control of motor outputs related to sexual behavior as demonstrated by prominent connections between the mPOA and the periaqueductal gray [11]. Because the PAG also displays multiple connections with more caudal mesencephalic and pontine structures [12], this brain structure is though to represent a premotor nucleus connecting the forebrain with specific brainstem nuclei as part of a network involved in the control of male sexual behavior [6].…”
Section: Effects Of Anosmia And/or Cloacal Gland Anesthesia On Fos Exmentioning
confidence: 99%
“…We have instead observed a reciprocal activation within the hippocampus/parahippocampus and the LMN, and there was no activity difference between the groups in our control area, the preoptic area, which plays a role in controlling sexual behaviour (e.g. Balthazart and Ball, 2007;Panzica et al, 1996) but has not as yet been shown to be involved in orientation tasks.…”
Section: Discussionmentioning
confidence: 57%
“…4 A and C). These areas are known to be important to associative learning, motivation, and autonomic functions including hunger in vertebrates (17,24), which suggests that crows perceived the association established between their caretakers and food. In crows, as in other animals including humans, it appears that both the striatum and the amygdala are critical to associative learning, with the former apparently broadly attuned to prediction errors and the latter often attuned to the reliability of threatening cues (16,20).…”
Section: Resultsmentioning
confidence: 99%